“They’ve killed the dogs!”: Land, literature and canines in contemporary Zimbabwe - Dan Wylie (Tydskrif vir Letterkunde, 2018)
This article explores the positioning of the dog in representations of farm takeovers in Zimbabwe between 2000 and 2017. It highlights the localised embeddedness of animal lives within social processes at a specific juncture of postcolonial history. The article focuses particularly on this moment marked by abrupt reversals of power, geographical distributions of people and animals, and the erasure of many physical and psychological borderlines. It focuses particularly on two novels, Graham Lang’s Place of Birth (2006) and Ian Holding’s Unfeeling (2005). It examines ways in which dogs feature as both physical presences and as psychological refractors for human responses to the violent invasions depicted in these novels. Animals of all kinds have been largely neglected in studies of the land-appropriation process, and the article gestures towards the fruitful combination of animal studies and an historically-situated, multispecies, postcolonial ecocriticism.